The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1073/pnas.1232420100
|View full text |Cite
|
Sign up to set email alerts
|

Runx3 and Runx1 are required for CD8 T cell development during thymopoiesis

Abstract: The RUNX transcription factors are important regulators of lineagespecific gene expression. RUNX are bifunctional, acting both as activators and repressors of tissue-specific target genes. Recently, we have demonstrated that Runx3 is a neurogenic transcription factor, which regulates development and survival of proprioceptive neurons in dorsal root ganglia. Here we report that Runx3 and Runx1 are highly expressed in thymic medulla and cortex, respectively, and function in development of CD8 T cells during thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
356
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(380 citation statements)
references
References 49 publications
18
356
2
1
Order By: Relevance
“…21 These findings are likely explained by the truncated Runx2 protein acting via a dominant negative effect 42,45 on the Runt-related family members in addition to Runx2, especially Runx1 and Runx3 that share the same highly conserved Runt DNA binding domain and are involved in regulating monocyte/macrophage biology. [46][47][48] Along these lines, recent studies have shown transdifferentiation of SMCs into a lipid-loaded, foam cell-like state during atherosclerosis. [49][50][51] These studies suggest that SMCs may not only contribute to fibrous cap formation and calcification but also directly participate in the process of atheroma formation through macrophage foam cell formation, accounting for $18-40% Mac2/CD68-positive cells observed in human and mouse atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 These findings are likely explained by the truncated Runx2 protein acting via a dominant negative effect 42,45 on the Runt-related family members in addition to Runx2, especially Runx1 and Runx3 that share the same highly conserved Runt DNA binding domain and are involved in regulating monocyte/macrophage biology. [46][47][48] Along these lines, recent studies have shown transdifferentiation of SMCs into a lipid-loaded, foam cell-like state during atherosclerosis. [49][50][51] These studies suggest that SMCs may not only contribute to fibrous cap formation and calcification but also directly participate in the process of atheroma formation through macrophage foam cell formation, accounting for $18-40% Mac2/CD68-positive cells observed in human and mouse atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] These studies suggest that SMCs may not only contribute to fibrous cap formation and calcification but also directly participate in the process of atheroma formation through macrophage foam cell formation, accounting for $18-40% Mac2/CD68-positive cells observed in human and mouse atherosclerotic lesions. 49 to control myeloid differentiation necessary for monocyte/macrophage and osteoclast formation, [46][47][48] their transcriptional activities may also be critical in controlling the SMC to macrophage/foam cell-like differentiation. Therefore, the dominant negative effect of truncated Runx2 in both bone marrow-derived cells and SMCs could act synergistically to prevent atheromatous plaque formation as seen in the Sun et al 21 study, though a detailed mechanism would require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other transcription factors have also been implicated in CD4/CD8-lineage commitment, including GATA-3, which is required for CD4-lineage development (5-7), TOX that can direct CD8-lineage development (8), and Runx3, which is involved in silencing CD4 gene expression in CD8-lineage cells (9,10).…”
Section: Compared With Mhc Class I (Mhc-i)mentioning
confidence: 99%
“…RUNX1 and RUNX2 are essential for hematopoiesis and osteogenesis, respectively, and are often mutated in leukemia and bone disease (Okuda et al, 1996;Lee et al, 1997;Look, 1997;Mundlos and Olsen, 1997;Otto et al, 1997). RUNX3 is involved in neurogenesis Levanon et al, 2002) and thymopoiesis (Taniuchi et al, 2002;Woolf et al, 2003), and it functions as a tumor suppressor in gastric cancer (Guo et al, 2002;Li et al, 2002;Kim et al, 2005b;Ito et al, 2008). RUNX3 regulates target gene expression by forming a complex with Smads, the transducer of TGF-b signaling.…”
Section: Introductionmentioning
confidence: 99%